Kriptografi Citra Menggunakan Metode Rivest-Shamir-Adleman Chinese Remainder Theorem Di Konsultan XYZ - Eko Budi Setiawan; Yogie Setiawan Nugraha (Ultimatics : Jurnal Teknik Informatika, 2015)
This study basically do image management processes which have no restrictions in about permissions to view the images on the XYZ consultant. This results in image can be easily used by those who do not have the right to open it. Therefore, security research digital image with cryptographic techniques using Rivest Shamir-Adleman With the Chinese Remainder Theorem (RSA-CRT) aims to provide restrictions permissions to view the image, and give the number of restrictions to view images that can be performed by the client. Results of this research is a security application that can create digital images can not be seen without using a specific key and restrictions as well as providing an image to only be opened in a few times. Index Terms— Cryptography, Digital Image, RSACRT, Data Security, Asymmetric Key